(untitled) (International Journal of Engineering and Computer Science, 2017)
Bluetooth is still a relatively new technology to the wireless world. It is designed for wireless communication between a wide variety of different Bluetooth enabled devices; from computers and PDAs to GPS systems and heart monitoring devices. There are a growing number of companies continually adopting this technology. As Bluetooth becomes a standard feature in many products that we use every day, it seems that the use of the technology will grow even faster in the future. [2] Unlike most devices, Bluetooth enabled devices communicate with each other automatically. There is no need to specify what type of action to take place or when it should to happen. When two devices are within range of each other, they will communicate back and forth to determine if there is any information to be passed. Messenger applications are very much in vogue these days. Whatsapp, WeChat, Hangouts, etc are a rage in the app world. But all these messenger applications exploit either mobile data which is a paid service or WiFi which is not always available and when available the connection strength fluctuates from place to place. Even when one wants to send a message to another person on the same floor or a few feet away they have to rely on the availability of these two. Hence we develop a Bluetooth based android chat application. Apart from general messaging between to users, the application also has an additional feature which allows users to save their chat history to an Android based server for storage thus not crunching on the phone memory as well.